2019
DOI: 10.26434/chemrxiv.9919022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly Selective, Amine-Derived Cannabinoid Receptor 2 Probes

Abstract: The endocannabinoid (eCB) system is implied in various human diseases ranging from central nervous system to autoimmune disorders. Cannabinoid receptor 2 (CB<sub>2</sub>R) is an integral component of the eCB system. Yet, the downstream effects elicited by this G protein-coupled receptor upon binding of endogenous or synthetic ligands are insufficiently understood—likely due to the limited arsenal of reliable biological and chemical tools. Herein, we report the design and synthesis of CB<… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Starting from a high-affinity recognition element, such as 1, [38] choice of the exit vector and linker-type for fluorophore attachment is considered the main challenge to ensure high affinity and selectivity. [40,41] We have recently reported that 7-nitrobenzofurazan (NBD) probe 2 shows excellent affinity to hCB2R (hCB2R Ki = 4.2 nM), paired with high selectivity over hCB1R (hKi ratio CB1R/CB2R >2000), suggesting a linker strategy for chemical probes based on amine 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Starting from a high-affinity recognition element, such as 1, [38] choice of the exit vector and linker-type for fluorophore attachment is considered the main challenge to ensure high affinity and selectivity. [40,41] We have recently reported that 7-nitrobenzofurazan (NBD) probe 2 shows excellent affinity to hCB2R (hCB2R Ki = 4.2 nM), paired with high selectivity over hCB1R (hKi ratio CB1R/CB2R >2000), suggesting a linker strategy for chemical probes based on amine 1.…”
Section: Resultsmentioning
confidence: 99%
“…[40,41] We have recently reported that 7-nitrobenzofurazan (NBD) probe 2 shows excellent affinity to hCB2R (hCB2R Ki = 4.2 nM), paired with high selectivity over hCB1R (hKi ratio CB1R/CB2R >2000), suggesting a linker strategy for chemical probes based on amine 1. [38] However, the NBD dye such as in 2 is not ideal for most imaging experiments due to its unfavorable photophysical properties (absorption/excitation maxima <500 nm, causing interference with lipofuscin-dependent tissue auto-fluorescence), low photostability and the pronounced sensitivity of quantum yields to medium polarity. [42] Thus, a series of fluorescent probes 3a-5 was prepared (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations